AL-QURAN AYAT MUHKAM DAN MUTASYABIH, SERTA SIKAP ULAMA - Marwaji, Deden; Sagala, Rumadani (Jurnal Pendidikan Bahasa Arab L-DHAD, 2024)
Abstract This research discusses the concept of muhkam and mutasyabih verses in the Qur'an and the attitude of scholars towards these two types of verses. The muhkam verse, which has a clear and unequivocal meaning, serves as the main guideline in religious practice, while the mutasyabih verse, which contains ambiguity, requires deep interpretation and understanding. This study uses a qualitative approach with literature analysis to explore the views of scholars regarding the importance of both types of verses in the context of Islamic law and education. The results of the study show that a proper understanding of the muhkam and mutasyabih verses is very important to avoid misunderstandings in the interpretation of Islamic teachings. Scholars have a variety of approaches to interpreting these verses, from those that are receptive without further interpretation to those that encourage critical analysis. This finding emphasizes the need for awareness among Muslims to understand the context and meaning of the verses of the Quran in order to practice religious teachings correctly.. Keywords: Muhkam Verses, Mutasyabih Verses, Al-Quran, Attitude of Ulama.